Development of the Inner City attitudinal assessment tool (ICAAT) for learners across Health care professions - McKinney, Mark; Smith, Katherine E; Dong, Kathryn A; Babenko, Oksana; Ross, Shelley; Kelly, Martina A; Salvalaggio, Ginetta (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Many health professions learners report feeling uncomfortable and underprepared for professional interactions with inner city populations. These learners may hold preconceptions which affect therapeutic relationships and provision of care. Few tools exist to measure learner attitudes towards these populations. This article describes the development and validity evidence behind a new tool measuring health professions learner attitudes toward inner city populations. Methods Tool development consisted of four phases: 1) Item identification and generation informed by a scoping review of the literature; 2) Item refinement involving a two stage modified Delphi process with a national multidisciplinary team (n = 8), followed by evaluation of readability and response process validity with a focus group of medical and nursing students (n = 13); 3) Pilot testing with a cohort of medical and nursing students; and 4) Analysis of psychometric properties through factor analysis and reliability. Results A 36-item online version of the Inner City Attitudinal Assessment Tool (ICAAT) was completed by 214 of 1452 undergraduate students (67.7% from medicine; 32.3% from nursing; response rate 15%). The resulting tool consists of 24 items within a three-factor model – affective, behavioural, and cognitive. Reliability (internal consistency) values using Cronbach alpha were 0.87, 0.82, and 0.82 respectively. The reliability of the whole 24-item ICAAT was 0.90. Conclusions The Inner City Attitudinal Assessment Tool (ICAAT) is a novel tool with evidence to support its use in assessing health care learners’ attitudes towards caring for inner city populations. This tool has potential to help guide curricula in inner city health.